Keputusan Pembelian Konsumen: Perspektif Online Consumer Review - Idris Yunus; Ariawan Ariawan (PRAGMATIS, 2022)
Information becomes a very important factor and influences consumers in making decisions. Before consumers buy products on online shopping sites, consumers are accustomed to looking for information in various ways, one of which is looking at information from online consumer review reviewers. The purpose of the study was determine purchasing decisions based on reviews from consumers who had purchased the product. This type of research uses descriftive and verification research with a population of 34,242 followers @Mirashop_gtlo. The slovin was used to determine a sample of 99 followers. Primary and secondary data collected through documentation and questionnaires were tested for validity and reliability. Multiple regression analysis as a statistical test tool. The results showed that all components of online consumer reviews influence consumer purchasing decisions. Source credibility is the main factor influencing consumer purchasing decisions.